Atlas of Southeast Europe : Geopolitics and History. Volume Two: 1699-1815. - Hötte, Hans H. A. (Handbook of Oriental Studies. Section 1 The Near and Middle East, 2016)
This atlas offers a survey of the history of Southeast Europe from 1699 until 1815, from the Treaty of Karlowitz until the eve of the Second Serbian Uprising. It covers modern-day Hungary, Slovenia, Croatia, Serbia, Kosovo, Macedonia, Bosnia and Herzegovina, Montenegro, Romania (Wallachia and Transylvania), Dalmatia, Greece and Cyprus.